THE ROLE OF REAL WORK COLLEGE (KKN) STUDENTS IN MANAGING USED PLASTIC BOTTLES IN SENDAGARAN GRESIK VILLAGE - Mubarok, Insani Wahyu (Universitas Muhammadiyah Surabaya, 2024)
The environment plays an important role for the survival of mankind and all living things on earth and the environment must be preserved. Humans who live on earth are not alone but together with other creatures, who have needs and depend on each other. Community service activities in the Nayata Work Lecture at Muhammadiyah University of Surabaya are carried out in accordance with existing themes, starting from the stage of identifying waste-related problems to implementing activities. Implementation of socialization and training activities for household organic waste processing in Sedagaran Village as an effort to minimize waste being thrown out of the house, especially if it is thrown carelessly, which can cause problems for the environment and society. Enthusiasm was also seen from the participants who attended the activity, namely from their involvement in taking part in the activity. Overall, participants actively asked questions regarding materials for processing and making compost from household organic waste and other sources of organic waste.